A Rare Complex Case of Congenital Umbilical Arteriovenous Malformation and Review of Literature - Rebeca Gregorio-Hernández; Ester Sanz-López; Alejandra Aguado-Del Hoyo; Gema Manrique-Martín; Juan Carlos De-Agustín; Manuel Sánchez-Luna (Thieme Medical Publishers, Inc., 2016)
Abstract Introduction Congenital umbilical arteriovenous malformations (AVMs) are extremely rare. We present the first case of congenital umbilical AVM with feeding arteries originating not only from abdominal but also from the mammary arteries. Case Report A 34-week gestational age newborn was transferred to our hospital with a supraumbilical murmur. Abdominal Doppler ultrasound (US) showed a large vascular AVM, with multiple feeding arteries and several venous drainage structures to the umbilical vein and also a persistent ductus venosus. She developed signs of heart failure on the 12th day of life. Computed tomography angiogram revealed an umbilical congenital AVM with feeding arteries originating from the external iliac, hypogastric, epigastric, and mammary arteries and a dilated umbilical vein draining the cluster. Also, a patent ductus venosus was observed. At 14 days of life, laparotomy was performed but due to the complexity of the feeding arteries of the AVM, complete exeresis was not performed, but only ligation of these arteries was made, to reduce the surgical risk. Conclusion To our knowledge, this is the first time that no complete excision was made but only ligation of the arteries. The infant was discharged home on postoperative day 14 being asymptomatic. Follow-up Doppler US showed thrombosed vascular structures.